Geography, education and citizenship: which citizenship interests us? - Basílio, Edvar Ferreira; Araújo, Raimundo Lenilde de; Oliveira, Alexandra Maria de (Debates em Educação, 2023)
This study has as objective discuss the Geography’s teaching under the perspective of the education for the exercise of territorial citizenship. Under the methodological point of view, a qualitative approach with documental investigative and bibliographical basis was utilized. Initially, the Brazilian educational legislation was analyzed and it was verified that in the legal marks of Education of Brazil the possibility of practicing citizenship finds itself strictly related and very limited to the capacity of the individual being tied to the world of work/job, and, for consequence, to consumption. The teaching of geography has much to favor the (re)construction of a citizenship that extrapolates the guarantee of civil and political rights, specially to enable socially engaged individuals.